2018
DOI: 10.1002/alr.22270
|View full text |Cite
|
Sign up to set email alerts
|

Blood eosinophils may predict radiographic sinus opacification in patients with chronic rhinitis

Abstract: Background:The association between chronic rhinosinusitis (CRS) and chronic rhinitis remains unclear. The aim of this study was to estimate the predictive factors for sinus opacification in chronic rhinitis patients without obvious CRS. Methods:We retrospectively studied a total of 332 adult patients with chronic rhinitis who visited our clinic from January 2015 to December 2017. All of the patients underwent endoscopic examination, allergy test, and osteomeatal-unit computed tomography. The subjects were assi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Therefore, peripheral blood eosinophil count has been incorporated into clinical prediction models by other studies. For example, peripheral blood eosinophil count is significantly associated with chronic rhinosinusitis in patients with chronic rhinitis ( 25 ). Peripheral blood eosinophil count less than 0.144 × 10 9 /L or 2% can predict a longer hospital length for patients who were admitted to the hospital with acute exacerbations of chronic obstructive pulmonary disease ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, peripheral blood eosinophil count has been incorporated into clinical prediction models by other studies. For example, peripheral blood eosinophil count is significantly associated with chronic rhinosinusitis in patients with chronic rhinitis ( 25 ). Peripheral blood eosinophil count less than 0.144 × 10 9 /L or 2% can predict a longer hospital length for patients who were admitted to the hospital with acute exacerbations of chronic obstructive pulmonary disease ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Blood eosinophil has been previously related to disease burden and outcomes of CRS, and asthma and eosinophilic granulomatosis with polyangiitis. [9][10][11][12][27][28][29] Despite studies indicating distinct endotypes in CRS patients, 30,31 our study aimed to understand the associations between uncontrolled disease and inflammatory patterns. We analyzed potential predictors in Chinese CR-SwNP patients and subgroups classified based on the site of eosinophilia.…”
Section: Discussionmentioning
confidence: 99%
“…After adjusting for confounding factors, we found that blood eosinophilia was a predictor of uncontrolled disease after surgery in patients with CRSwNP. Blood eosinophil has been previously related to disease burden and outcomes of CRS, and asthma and eosinophilic granulomatosis with polyangiitis 9–12,27–29 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, during host defense, eosinophils produce a variety of chemical mediators that can induce detrimental effects on the host. Elevated blood eosinophil counts correlated with tissue eosinophilic inflammation and to the disease severity and the recurrence of CRS after sinus surgery [ 22 , 23 ]. Eosinophil counts in peripheral blood might be a biomarker for severe intractable CRS with type 2 inflammation.…”
Section: Introductionmentioning
confidence: 99%